(untitled) (Research, Society and Development, 2021)
Anacardium occidentale L. is a tree species in the Family Anacardiaceae, found in many countries. In Brazil, it is popularly known as "cashew", "purple cashew", being considered a native Brazilian species that has wide distribution throughout the national territory. Therefore, the aim of this study was to evaluate the effect of maternal treatment with A. westerne extract on maternal toxicity and postnatal development of rat offspring. A preliminary phytochemical study of the plant was carried out, in which qualitative tests were performed to identify alkaloids, flavonoids and tannins through classical staining and precipitation reactions. Primiparous female wistar rats, aged between 90 and 120 days, and weighing 200 days were ± 50g. The rats were mated for 24 hours, being one female for each male. After confirming pregnancy, pregnant rats were housed in individual maternity cages, randomly divided into two groups: CONTROL Group (n=9) that received water distilled by gavage; and EXTRACT group (n=9), which received the dose of 100mg/kg of the crude extract of Anacardium occidentale, by gavage from the first day of gestation until the end of lactation. During pregnancy, the signs of toxicity of the progenitors and the somatic and physical development of the offspring were evaluated. The results of this study indicate that the administration of hydroalcoholic extract from the purple cashew leaf affected the physical and somatic development of the offspring, suggesting a neonatal toxic effect. In addition, this extract also induced systemic maternal toxicity, characterized by the presence of clinical signs of toxicity.